1993
DOI: 10.1029/93jd02056
|View full text |Cite
|
Sign up to set email alerts
|

A general circulation model study of the effects of faster rotation rate, enhanced CO2 concentration, and reduced solar forcing: Implications for the faint young sun paradox

Abstract: Solar energy at the top of the atmosphere (solar constant), rotation rate, and carbon dioxide (CO2) may have varied significantly over Earth's history, especially during the earliest times. The sensitivity of a general circulation model to faster rotation, enhanced CO9. concentration, and reduced solar constant is presented. The control simulation of this study has a solar constant reduced by 10% the present amount, zero land fraction using a swamp ocean surface, CO9. concentrations of 330 ppmv, present-day ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
4
17
1
Order By: Relevance
“…In present-day conditions, a change in day length from 24 to 16 h causes a global mean surface warming of about 2 • C (from 14.5 to 16.3 • C, Appendix Fig. A1), in agreement with previous results (Jenkins, 1993b). However, the warming is not homogeneous.…”
Section: Effects Of Faster Earth Rotation Rate and Saltier Oceanssupporting
confidence: 81%
See 1 more Smart Citation
“…In present-day conditions, a change in day length from 24 to 16 h causes a global mean surface warming of about 2 • C (from 14.5 to 16.3 • C, Appendix Fig. A1), in agreement with previous results (Jenkins, 1993b). However, the warming is not homogeneous.…”
Section: Effects Of Faster Earth Rotation Rate and Saltier Oceanssupporting
confidence: 81%
“…The authors explained their results by the ice-albedo feedback, which is enhanced during the Archaean due to a faster Earth rotation rate. This result contrasts with conclusions obtained by Jenkins (1993b) and Jenkins et al (1993) with CCMAO (CC-MAO was the version of the NCAR model at the beginning of the 90s, an atmospheric GCM coupled to a swamp ocean without heat capacity), where a faster rotation rate would have induced a warmer climate. The recent modelling of Archaean climate by Charney et al (2013) using LMDz (an atmospheric GCM coupled to a slab ocean developed by Laboratoire de Météorologie Dynamique) challenged the CLIMBER results (Kienert et al, 2012(Kienert et al, , 2013 and revealed a very limited impact of the faster Earth rotation.…”
Section: Introductioncontrasting
confidence: 55%
“…30 spring tides/annum in the early Palaeoproterozoic, 26.2 in the late Cryogenian and 24.7 today; Williams, 2000. (2) A faster rotating Proterozoic Earth led to less efficient poleward transport of heat, with a slightly warmer equator and cooler poles (Kuhn et al, 1989;Jenkins, 1993), compounding the enigma of Proterozoic low-palaeolatitude glaciation. (3) The hypothesis that the orbital periods for precession and obliquity have increased with time due to secular increase in the Earth-Moon distance (Berger et al, 1989) is confirmed by the precession period of 19.6 ± 1.1 kyr and the obliquity period of 31.3 ± 3.0 kyr recorded by Late Ordovician-Early Silurian evaporites in Western Australia (Williams, 1991), compared to respective periods of 23 kyr and 41 kyr today.…”
Section: Solar System Mechanics and The Earth's Rotation Ratementioning
confidence: 99%
“…However, while these simulations are based on an atmospheric general circulation model (GCM), they do not involve full ocean or sea-ice modules. Furthermore, Jenkins (1993a) has reduced the solar constant compared to today by 10 and 15 % which does not correspond to the actual Archean values. Due to a limited number of simulations, no critical CO 2 partial pressure required to prevent the Earth's surface from fully freezing was explicitly identified in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, these models do not represent any 3-D effects as meridional heat transport or albedo changes due to continents, sea ice or clouds (Kasting, 2010). A few early studies of the Archean climate applied 3-D models (Jenkins, 1993a(Jenkins, , 1996. However, while these simulations are based on an atmospheric general circulation model (GCM), they do not involve full ocean or sea-ice modules.…”
Section: Introductionmentioning
confidence: 99%